Nowatorstwo i eksperyment w poezji późnego baroku - Pieczyński, Maciej (Śląskie Studia Polonistyczne, 2019)
Religious poetry of the Saxon times has often in the past prompted quite radical, and at the same time emotional, valuations coming from scholars. Its distinctness from the literature of the preceding periods was also frequently underscored. The present article attempts to expand upon the issue of novelty and unique features of the works by late Baroque religious poets (Stanisław Brzeżański, Franciszek Gniewisz, Karol Mikołaj Juniewicz, Hieronin Falęcki, and Józef Baka). What is assumed to have been characteristic of the said literature is the endeavour at maximal persuasive efficacy and presence of deep internal tensions between christianitas and humanitas.